EFFECT OF ELECTRONIC COMMERCE ON THE DEVELOPMENT OF UZBEKISTAN'S FOREIGN TRADE (Multidisciplinary Journal of Science and Technology, 2025)
The rapid development of digital technologies has significantly changed global trade, introducing new models such as electronic commerce (e-commerce). Uzbekistan, a landlocked country in Central Asia, is adopting e-commerce as an important tool for promoting foreign trade. This article examines the transformative impact of e-commerce on Uzbekistan's foreign trade, including its contribution to export diversification, market expansion, and trade efficiency. The analysis also identifies persistent challenges such as infrastructure gaps, regulatory constraints, and limited awareness of e-commerce, while suggesting comprehensive strategies for harnessing the full potential of e-commerce for economic growth.